Bilingualism in English as a Foreign Language (EFL) Classroom Context - Siti Patonah; Rifki Irawan (FOSTER: Journal of English Language Teaching, 2022)
This study explores the process and obstacles of bilingualism at SMP Muhammadiyah 3 Yogyakarta. The research was descriptive qualitative research. The samples of this research were 20 students. The data used were collected from observation, questionnaires, interviews, and documentation. This data sources were students of grade VIII and one English teacher at SMP Muhammadiyah 3 Yogyakarta. Data analysis was performed using a Linker's scale for questionnaire data, data reduction, data presentation, verification, and conclusions. The results showed that students' interactions with students and students with teachers in the bilingual class of SMP Muhammadiyah 3 Yogyakarta in the learning process were still ineffective and experienced difficulties that hinder the interaction process. The findings were as follows (1) Students still felt insecure if they had to use full of English to interact with friends in a bilingual class, they still felt afraid of mispronouncing English correctly and adequately, they did not master vocabulary well, and they used English in bilingual with the teacher only in the classroom. (2) The obstacles that students experienced in the teaching and learning process in a bilingual class as follows: Students still felt ashamed to use English to interact in a bilingual class, they still taught that using English was not a necessity in a bilingual class, sometimes, Bahasa Indonesia was still a language to interact with friends, and they were still afraid of using English by with excellent and correct English in pronunciation.